Dynamic Analysis for Overturning of Pile Driving Machine, etc., on Soft Ground - Toma, Shouji; Seto, Kenji; Chen, Wai Fah (Transactions on Engineering and Computing Sciences, 2023)
There were quite a few overturning accidents of heavy machinery which have a high center of gravity such as pile driving machines, cranes, jacks, or working vehicles with aerial platform. Researches to study the background of the accidents have taken place from the structural stability point of view by the authors. The structural instability, as can be seen typically in the elastic buckling of columns, may be a blind spot because the structures deflect in different directions to that of the load, which makes it difficult to predict. According to the past investigations, the overturning mechanisms can be categorized into the three: (1) Type of overturning moment, (2) Type of structural instability and (3) Type of equilibrium transition, in which Type of equilibrium transition plays important role on the overturning on soft ground. The past investigations were based on the static analysis. Dynamic analysis is essential to include the effect of inertial forces which will significantly affect the overturning accidents on the soft ground. In the static analysis, the displacement inclination is considered to stop at the equilibrium position, but in the dynamic analysis it will continue increasing due to the inertial force. Then, it is possible the displacement may go beyond the equilibrium and even the stability limit to overturn. In this paper, the equations of motion will be first introduced, then behaviors of the machinery from time to time, i.e., the inclination-time curves, will be obtained by solving the equations. It is shown that the dynamic analysis can explain more precisely the overturning behaviors of the machinery on the soft foundation than the static analysis.